Polyoxometallates as effective photocatalysts in water purification from pesticides - E. Gkika; P. Kormali; S. Antonaraki; D. Dimoticali; E. Papaconstantinou; A. Hiskia (International Journal of Photoenergy)
Polyoxometallates (POM), i.e., metal oxide clusters of mainly tungsten are effective homogeneous photocatalysts for the mineralization of organic pollutants. POM are, at least, as effective as the well studied TiO2. OH⋅radicals formed by the reaction of the photo-excited polyoxometallates with H2O, appear to play a key role in the process. In this study, the photocatalytic activity of POM have been tested on some diversified pesticides of interest such as lindane, bentazone and fenitrothion to determine the feasibility of decontamination of aqueous solutions from these pollutants. The results show that aqueous solutions containing the above pesticides, upon photolysis in the presence of polyoxotungstates undergo effective degradation to CO2, H2O and the corresponding inorganic anions. The intermediates identified give rise to complicated degradation mechanisms prior to mineralization. The characteristic reactions that take place consist of hydroxylation, H-abstraction, dehalogenation, denitration, desulfurization, breaking of the C-C bond etc.